Diversity and Distribution of Cyprinid Fishes in Tapi Upstream System - เลิศสุทธิชวาล, ธีรวุฒิ; ขวัญใจ, จันทนา; ขวัญใจ, จันทนา (Journal of Applied Research on Science and Technology (JARST), 2016)
Diversity and distribution of Cyprinidae in Tapi upstreams were investigated during 2012 - 2014. Sixteen localities from three provinces were assigned as fish collection sites, Suratthani (6 stations), Nakhonsithammarat (4 stations) and Krabi (6 stations). In this study 26 genera and 36 species of Cyprinidae were identified and confirmed according the Fishbase (2016). Krabi has the highest number of fish species (25 spp.), followed by Nakhonsithammarat and Suratthani (21 spp.). Of 36 fish species collected, 11 species were distributed in all three provinces, while 15 species were present in each province, Krabi (8 spp.), Nakhonsithammarat (4 spp.) and Suratthani (3 spp.).